China's Emerging New Economy : the Internet and E-Commerce. - Wong, John (World Scientific Publishing Company, 2000)
The New Economy has hit China, driven by the Internet and e-commerce. China has made a good start in both areas. Since its debut, subscribers to the Internet grew exponentially from a mere 1,600 in 1994 to 16.9 million in mid-2000. E-commerce transactions registered a total revenue of 200 million yuan in 1999, or twice as much as in 1998. B2C e-commerce is expected to grow by 300% in 2000. However, the rapid growth of the sectors is constrained by factors such as a small base of registered users, high costs of using the Internet, government control of information access, and lack of an effecti.